Effect of Iron Application on Yield of Turmeric (Curcuma longa) in Maharashtra, India - Kamble, B. M.; Kadam, J. H.; Kathmale, D. K. (International Journal of Bio-resource and Stress Management, 2023)
The field experiments were conducted during 2006-12 at Agricultural Research Station, Kasabe Digraj, Dist-Sangli, Maharashtra, India to study the effect of iron application on growth, soil fertility, yield and curcumin of turmeric cv. Phule Swarupa. The experiment was laid out in a randomized block design with seven treatments and four replications. The treatments consisted of control, general recommended dose of fertilizer (GRDF) i.e. 200: 100:100 N:P2O5:K2O kg ha-1+25 t FYM ha-1, GRDF+10 kg FeSO4 ha-1 , GRDF+20 kg FeSO4 ha-1 soil application (50% at the time of planting and 50% at the time of earthing-up), GRDF+1% FeSO4 foliar spray after planting at monthly interval, GRDF+1% FeSO4 foliar spray after planting at bimonthly interval and GRDF with FYM 50 t ha-1. The results revealed that the significantly highest fresh rhizome yield (337.9 q ha-1), dry yield (70.3 q ha-1), height of plant (95.6 cm), number of leaves plant -1 (10.6 ) and number of tillers-1 (4.4) was recorded in GRDF+20 kg FeSO4 ha-1 soil application as compared to control. The significantly highest soil pH and electrical conductivity were recorded in control at harvest. The significantly maximum available N and DTPA Fe in soil were noticed in GRDF+FYM 50 t ha-1. The significantly highest DTPA Zn and Cu were recorded in GRDF+20 kg FeSO4 ha-1 soil application as compared to control. The soil application of 20 kg FeSO4 ha-1 or four sprays of 1% FeSO4 along with GRDF to turmeric can be recommended for getting the highest yield, monetary benefits and maintaining soil fertility.